PENGARUH MINUMAN ISOTONIK TERHADAP DAYA TAHAN AEROBIK - rika sepriani; Sepriadi Sepriadi (Jurnal Sporta Saintika, 2020)
The purpose of this research is to prove the benefits of isotonic drinks promised by the manufacturers. This is a quasi-experimental research design involving 20 non-athlete male students. The data were analyzed using t-test.From the data analysis, it was found that there was a significant difference between aerobic endurance before and after drinking isotonic drinks, tobserve (5.398604) > ttable (1.729) at level significant α = 0.05. Based on the result of the research, it can be concluded that isotonic drinks has a significant effect towards students’ aerobic endurance.